Peningkatan Kemampuan Menulis Resensi Novel Dengan Menggunakan Model Pembelajaran Kooperatif Tipe Student Teams Achievment Division (STAD) Pada Siswa SMA Global Prima - Yolanda Novita Silaban (Jurnal Bahasa Indonesia Prima (BIP), 2024)
Mastery in writing a novel review is needed because a good and correct review can provide a clear picture of the novel being reviewed for the reader and encourage the reviewer to participate in reading the novel being reviewed. The existence of essential competencies in writing novel reviews at the Senior High School level in the Education Unit Level Quirkulum (KTSP) is a form of government attention to the importance of student mastery in the ability to write novel reviews. From the problems that occur in Indonesian language learning, a learning model is needed to improve the ability to write novel reviews and improve learning outcomes. The Student Teams Achievement Division (STAD) Cooperative learning model can overcome the problems of writing novel reviews. This research was conducted using the Classroom Action Approach (PTK). Action research is the application of fact finding to problem solving in social situations to improve the quality of the actions taken therein, which involves collaboration and cooperation of researchers, practitioners, and lay people.